2013
DOI: 10.1111/1468-2427.12001
|View full text |Cite
|
Sign up to set email alerts
|

Gentrification, Education and Exclusionary Displacement in East London

Abstract: In this article we draw on Peter Marcuse's discussion of different types of displacement using evidence from a recent study we conducted in East London to argue that there is clear evidence of ‘exclusionary displacement’ and ‘displacement pressure’ in terms of education and specifically the choice of schooling. We show how the incoming middle classes in the Victoria Park area of inner East London have displaced not only existing poor residents but also many of the less affluent middle class from the favoured s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 30 publications
4
59
0
5
Order By: Relevance
“…Finally, several scholars, most notably in Europe, have emphasized how middle‐class families can leverage residential choices to their advantage in the urban educational market (Butler, Hamnett, and Ramsden ; Gramberg ; Hamnett and Butler ). In their study of one East London neighborhood, for example, Butler, Hamnett, and Ramsden () found that new middle‐class residents made strategic housing decisions that would enable their children to enroll in the school of their choice. In light of a student assignment policy that privileged proximate families, these parents' actions displaced existing poor and less affluent middle‐class students from highly favored schools in the area.…”
Section: Mapping the Literature On Middle‐class Families And Urban Pumentioning
confidence: 99%
“…Finally, several scholars, most notably in Europe, have emphasized how middle‐class families can leverage residential choices to their advantage in the urban educational market (Butler, Hamnett, and Ramsden ; Gramberg ; Hamnett and Butler ). In their study of one East London neighborhood, for example, Butler, Hamnett, and Ramsden () found that new middle‐class residents made strategic housing decisions that would enable their children to enroll in the school of their choice. In light of a student assignment policy that privileged proximate families, these parents' actions displaced existing poor and less affluent middle‐class students from highly favored schools in the area.…”
Section: Mapping the Literature On Middle‐class Families And Urban Pumentioning
confidence: 99%
“…In densely populated neighbourhoods, the frameworks of space use are transgressed via practices of racial and class privilege embodied in the occupation of space under conditions of gentrification (Butler, Hamnett, & Ramsden, 2013;Drew, 2011;Garbin & Millington, 2012;Jackson & Benson, 2014;Wilson & Grammenos, 2005). The experience of difference is marked by everyday grievances often centred on the breaching of expected codes of conduct.…”
Section: Reflexivity and The Breaches Of Encountermentioning
confidence: 99%
“…We were not criticizing a career's worth of work (cf. Butler, Hamnett, and Ramsden 2013). The resort to writing about inequality elsewhere is important though, since it helps to further demonstrate the problematic ways in which class and inequality are treated in both their 2008 paper and recent rebuttal.…”
Section: Davidson and Wyly: Class Analysis For Whom? 301mentioning
confidence: 99%